A Systematic Review of Sexual Assault Referral Centers (SARC) - Muhammad Kashif Butt, Muhammad Maqsood, Faizan Maqsood, Muhammad Zahid Bashir (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Sexual violence against women is a commonly prevalent human rights violation and a widespread public health problem. It is associated with substantial short and long-term ill consequences for women and their families. As the response of the community is increasing day by day to sexual assault, new interventions have evolved in the form of sexual assault centers. These centers are community-based organizations that work to counteract the potential negative impacts of sexual assaults on the physical, mental, and psychological health of the victims. Objective: The objective of the study is to find out the multi-disciplinary professional services provided by these centers globally to treat sexual assault victims. Methods: The information is collected from secondary sources. This systematic review was prepared according to the Preferred Reporting Items for Systematic Review and Meta-Analysis. Online databases were searched including, Research Gate, Taylor & Francis, Wiley Online Library, Scopus, and Google Scholar, and the search included the term ‘sexual assault centers, rape crisis centers, integrated services at sexual assault centers’. Results: The important post-assault services provided by these centers include medical treatment, forensic examination, police services, and psychological counseling to the sufferers of the tragic event. In addition, these centers are also involved in carrying out significant research and educational work. Practical Implication: These rape crisis centers are providing multidisciplinary services to rape victims including services of specially trained nurses, treatment and care of medical injuries, forensic medical examination, police services, counseling by psychologists and a highly organized follow-up. Conclusion: These centers are providing valuable multidisciplinary services including medical treatment, forensic examination, police services, and psychological counseling to the sufferers of sexual abuse under one roof. The understanding of these multidisciplinary services could be used to endorse the development of sexual assault centers in different parts of the world Keywords: Sexual assault, sexual assault centers, multidisciplinary services